Introduction to “Gatekeeper's state: immigration and boundary policing in an era of globalization” - Palafox, Jose (Social justice, 2001)
Part of a special issue on immigration and boundary policing in an era of globalization. The writer introduces the articles in this special issue, notes that they examine the intricacy of U.S.-Mexico border policing in terms of the effects of U.S. immigration and border policy on illegal migrants and on the well-being of American citizens.